Consumer payment preferences in the euro area - László Kajdi (European Central Bank (ECB), 2022)
Payments are a key focus of central banks, as - together with the safe, efficient operation of the payments market - wide access to cash is fundamentally important for a healthy economy. In this study, three main research areas were investigated: 1. socioeconomic characteristics that can be associated with financial inclusion; 2. factors behind consumers' payment choices; 3. underlying factors for holding cash in a wallet (i.e. for transactional purposes). Regression results for the first research question confirmed the findings of international literature, i.e. mainly older age, lower income and lower educational level is associated with the lack of access to electronic payment options. The study pursues various approaches to investigate consumer payments choices, and the results from most models showed that those with higher level of income and education, or lower level of cash income are more likely to prefer and actually use electronic payment methods. Finally, concerning the holding of cash the initial expectations were confirmed i.e. those who do not use cash for daily transactions tend to keep less cash in their wallet, while those who indicated preference for cash payments or higher importance of cash payment option are more likely to keep higher cash amounts.
Keywords: D11; D12; E42; J33; 330; payments; cash; financial inclusion